Tradisi Maisi Sasuduik dalam Perkawinan Masyarakat Minangkabau: : Studi Interaksi Adat dan Hukum Islam - Wati, Felia (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the sasuduik tradition in the minangkabau indigenous people, the influence of women’s social strata on the amount of “uang sasuduik”, the relationship between religion and custom, and its relevance to the marriage law. The maisi sasuduik tradition is the giving of a sum of money or goods that must be fulfilled by the man when he is about to marry a women based on an agreement made by the female ninik mamak and the male ninik mamak. This tradition only applies in Luhak Nan Limo Puluah which covers the entire Lima Puluh Kota and Payakumbuh City. This tradition is also called Adat Salingka Nagari because it only applies to one particular area and is not obligatory for other areas. This study departs from the theoretical framework of al-‘adah muhakkamah. Because, the maisi sasuduik tradition can be used as a behavioral attitude or habit in society. The research method used is qualitative research ehich uses more subjective qualitative with a legal anthropological approach that ficuses on studying the legal system in terms of human norms and culture. The main source for explaining this research is by conducting interviews with traditional leaders (datuak), cadiak pandai and indigenous people who understand the maisi sasuduik tradition in Nagari Andiang, Suliki District, Lima Puluh Kota District. Costoms and religion in Minangkabau Society cannot be separated as is the philosophy of life in Minangkabau: “Adaik basandi syarak, syarak basandi Kitabullah.”even though the maisi sasuduik tradition does not have written rules, the community still adheres to it because of the awareness of the law that exists in every individual in the community itself. Keywords: Maisi Sasuduik Tradition, Custom, Islamic Law, Minangkabau